Human development index based on Islamic values - Fachrunnisa, Olivia (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Human Resources is one of the most important assets. Human development emphasizes the strength and range of human choices, while HR development focuses on the power of creativity, pioneering, and productivity in the context of developing human resources. Actually, the development of human resources in the form of social processes is a facilitator in realizing human development. The human development index is proposed to evaluate, measure and compare the scale of a country's development is achieved from a harmonious average of the following three indices: (1) per capita income (measures the state of the economy and has worldly welfare); (2) life expectancy at birth (measures health situation); and (3) literacy level (measures the level of knowledge and wisdom).